EFEKTIVITAS EKSTRAK KULIT BUAH MANGGIS (Garcinia manggostana Linn) DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Streptococcus mutans - Ferry Gustiningrum; Arlina Nurhapsari; Recita Indraswary; Uswatun N.A Darjono (Jurnal Medali, 2013)
Caries known as disease which hard to lose. The major causative of caries is Streptococcus mutans bacteria. Streptococcus mutans can be inhibited by antibacterial agent. Substances in the pericarp of mangosteen fruit (Garcinia mangostana Linn) was reported had an antibacterial ability. These compounds such as xanthone, saponins, tannins and flavonoids. The purpose of this study was to examined the effectiveness of mangosteen pericarp extracts (Garcinia mangostana Linn) for inhibite the growth of Streptococcus mutans, which the major causative bacteria of dental caries.This study used experimental laboratory with 25 sample were divided into 5 groups concentration which are 3.125%, 6.25%, 12.5% , 25%, and 50%. Streptococcus mutans culture on blood agar and the disks have been soaked in the mangosteen pericarp extracts.The disks placed on the blood agar. Effectiveness of antibacterial mangosteen’s pericarp extract formed in the presence of inhibition zones around paper disc and measured with sliding calipers (mm). The average inhibition zone, analyzed with the Kruskal-Wallis test followed by Mann Whitney test.The result of this research was significant difference (sig<0,05) from the Kruskal-Wallis test with the probability 0,000. The Mann Whitney test result is also said significant (p<0,05).Conclusion of this study, the mangosteen pericarp extracts (Garcinia mangostana Linn) with minimal concentration 3.125% can inhibit Streptococcus mutans. Keywords: Anti bacterial effect, Mangosteen’s pericarp extract, Streptococcus mutans